Tibialis Anterior Tendon Entrapment After Ankle Tightrope Insertion for Acute Syndesmosis Injury. Issue 3 (June 2013) - Welck, Matthew James; Ray, Pinak
Ankle syndesmotic injuries often require anatomic reduction and fixation. Syndesmosis screw fixation is commonly used; however, this prevents physiological motion at the joint, often requires a second operation for screw removal, and may limit postoperative weight bearing. The Ankle Tightrope (Arthrex, Naples, FL) was introduced to allow physiological tibiofibular micromotion, early ankle range of motion, and weight bearing, and did not require a second operation for removal. For Maisonneuve injuries, or more severe syndesmosis instability, a second tightrope is required. This is advised to be placed 1 cm above the first with axial divergence in the coronal plane to increase rotational stability. Initial series have shown the main complications of tightrope fixation to be knot prominence or wound complications. Other documented complications include erosion of the buttons into bone, synostosis, and diastasis. This is the first report of tendon entrapment from the medial button. Reasons for this are discussed with suggestions for surgical technique. Levels of Evidence : Therapeutic, Level IV